Long‐term quality of life in older patients with HPV‐related oropharyngeal cancer. Issue 11 (13th November 2018) - Baxi, Shrujal S.; Cullen, Grace; Xiao, Han; Atoria, Coral L.; Sherman, Eric J.; Ho, Alan; Lee, Nancy Y.; Elkin, Elena B.; Pfister, David G.
Abstract: Background: We explored if age affects quality of life (QOL) in survivors of locally advanced human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (SCC). Methods: In a cross‐sectional survey of 185 patients, at least 12 months from radiation, we evaluated generic (EuroQOL‐5D questionnaire [EQ‐5D]) and head and neck specific (European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire‐Head and Neck 35‐questions [EORTC‐QLQ‐H&N35]) QOL questionnaires and compared differences between younger (<65) and older (≥65) patients. Results: The median age was 57.0 years (range 25‐77 years), and 31 patients (16.8%) were ≥65 years old. There was no significant difference in EQ‐5D global QOL scores by age ( P = .53). Patients ≥65 years reported more immobility ( P < .01), problems with social eating ( P < .0001), and coughing ( P < .01). Patients ≥65 years were not more likely to ever require a gastrostomy ( P = .24) but were more likely to remain gastrostomy‐dependent at the time of the survey ( P = .02). Conclusion: Despite similar generic QOL, older survivors may have more mobility problems and issues with social eating compared with younger survivors deserving of further evaluation.